2022
DOI: 10.17309/tmfv.2022.2.18
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Day Time on Cognitive Performances of Preadolescent Athletes Nurtured in a Controlled Environment

Abstract: Research purpose. The study aimed to examine how the cognitive performances of preadolescent sports trainees living and training under a controlled environment are affected during the three different day times. Materials and methods. The research involved 16 male sports trainees from the Jharkhand State Sports Promotion Society, Ranchi, who varied in age from 11 to 14 years and had a minimum of two years of training experience in the same academy. To assess cognitive performance like long-term focused at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 47 publications
0
2
0
Order By: Relevance
“…Conversely, other studies ( 48 , 49 ) have reported that cognitive performance is better in the morning than in the afternoon. Pahan and Singh ( 50 ) also reported that cognitive functioning in preadolescent athletes was unaffected by the time of day. These discrepancies may be attributed to factors such as chronotype (neither chronotype in our study), age (adolescent in our study), sex, and participant wake-up time ( 51 ).…”
Section: Discussionmentioning
confidence: 98%
“…Conversely, other studies ( 48 , 49 ) have reported that cognitive performance is better in the morning than in the afternoon. Pahan and Singh ( 50 ) also reported that cognitive functioning in preadolescent athletes was unaffected by the time of day. These discrepancies may be attributed to factors such as chronotype (neither chronotype in our study), age (adolescent in our study), sex, and participant wake-up time ( 51 ).…”
Section: Discussionmentioning
confidence: 98%
“…Data on school-aged children and adolescents are even scarcer (e.g., [38]), thus limiting our knowledge on how these factors affect children's cognitive assessments. Most studies on cognition with pediatric populations focus on sleep patterns or TOD or chronotype effects independently, not in interaction [38][39][40][41][42]. On top of the fact that the combined influence of TOD and individual differences on chronotype is still unclear in school-aged children, assessments via Teleneuropsychology (TeleNP) in children remain mostly unexplored.…”
Section: Introductionmentioning
confidence: 99%